Business and administration occupations : findings about differences and similarities in their requirements and mentalities - Kaiser, Franz [Verfasser]; Annen, Silvia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2017)
"The paper is based on findings of the research project at the German Federal Institute of Vocational Education and Training (BIBB). To find similarities and differences of these occupations, we used a broad methodological approach during a four-year project. This approach included a detailed qualitative analysis of all the training regulations and curricula for the training part in schools, an employee survey, a historical and sociological study, and comparative study of German-speaking countries. Our project revealed that the similarities between these occupation clearly outweigh the differences, with nearly all of them having in common controlling, accounting and commercial management, as well as processing information and communication with clients. On the other hand, though, a detailed analysis also showed a number of differences, such as the particular mentalities and competences in the various vocational branches. Based on the similarities between qualifications and on the findings of the comparative study, we suggest developing key curricula for all business and administration occupations. They would give qualified skilled workers more opportunities in the labour market and help to recognize the outcome of VET-based training for university degrees. Finally, a more critical look at the bundle of qualifications in those occupations opens a lack of ethical reflections concerning the way things in the economic business." (Authors' abstract ; BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; S 6.4.3 Organisations-, Verwaltungs-, Rechts- und Büroberufe; S 6 Berufsbereiche; G 1.2.3 Qualifikationsentwicklungen; Kaufmännischer Beruf; Dienstleistungsberuf; Berufsfeld Wirtschaft und Verwaltung; BIBB-/BAuA-Erhebung; Tätigkeitsmerkmal; Berufsbeschreibung; Berufsanforderung; Curriculum; Berufsforschung